Workplace learning in the Malaysian tourism sector determining competence development and job satisfaction among employees of small to medium-sized tourism enterprises - Shamuni Kunjiapu (Strategic Information and Research Development Centre New Era University College, 2021)
Lack of skills and innovative ability among employees hampers the competitiveness of an organisation regardless of its size. Yet human capital can be developed through workplace learning. This book explores workplace learning among employees of small to mid-sized tourism related enterprises. It looks at types of learning, factors that encourage it, competencies that are developed through it and job satisfaction as the outcome of participating in workplace learning. Based on quantitative and qualitative research, including interviews with employees, this book argues that informal learning is the foremost type of workplace learning, whilst the main factor encouraging workplace learning is the organisational culture. Findings also showed that soft competencies are by far the most important competencies developed and that there is a significant relationship between workplace learning, competencies developed and job satisfaction. This study establishes the importance of small to mid-sized tourism enterprises as a learning organisation. Besides this, it also urges organisations to rethink their workplace culture in order to encourage workplace learning, and encourages authorities to redesign training programmes for small to mid-sized organisations.